(untitled) (Journal of Asian Development Studies, 2024)
Vitamin-D deficiency (VDD) is a global public health issue affecting individuals across all age groups, including adolescents. It is primarily synthesized through skin exposure to sunlight, with dietary intake playing a supplementary role. Various sociodemographic factors, including maternal education, gender, and lifestyle, significantly influence vitamin-D levels. To evaluate the vitamin D levels of adolescents and investigate their associations with dietary habits and sociodemographic characteristics in patients attending outpatient clinics at Northwest General Hospital and Research Centre Peshawar, Pakistan. This cross-sectional study was conducted from June 2023 to March 2024 on 230 patients aged 15-50 years presenting with symptoms suggestive of vitamin D deficiency. Participants completed a structured questionnaire detailing sociodemographic information and dietary habits, while serum vitamin D levels were assessed using standard biochemical assays. Data were analyzed using SPSS version 25. The majority of participants (61%) were aged 15-35, and females constituted 63% of the sample. Only 26.8% had sufficient serum vitamin D levels, 37.7% were insufficient, and 35.5% were deficient. Maternal education significantly correlated with vitamin D status, as 52% of mothers had completed graduate or postgraduate studies. Dietary habits revealed limited consumption of vitamin D-rich foods, with the majority reporting infrequent intake. Vitamin D deficiency is highly prevalent among adolescents in the study population, with sociodemographic factors such as gender, maternal education, and dietary habits playing critical roles.